Shame, Publicity, and Self‐Esteem. (14th October 2014) - Galligan, Phillip
Abstract: Shame is a puzzling emotion. On the one hand, to feel ashamed is to feel badly about oneself ; but on the other hand, it also seems to be a response to the way the subject is perceived by other people. So whose standards is the subject worried about falling short of, his own or those of an audience? I begin by arguing that it is the audience's standards that matter, and then present a theory of shame according to which shame is a response to the subject's perception that he is not thought of in the way he intrinsically values himself for being thought of by someone else. Then I go on to suggest some refinements to this basic view. First, the subject of shame is primarily concerned about his audience's attitudes toward him, not what they believe about him. And second, there may be one particular attitude which he values himself for inspiring. There is no very perspicuous term for this attitude, so I call it 'proto‐respect' – the attitude a social animal directs toward those it regards as valuable allies or bad enemies.